PERAN SOFT SKILL DALAM MEMPERSIAPKAN FRESH GRADUATE MEMASUKI DUNIA KERJA: ANALISIS MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING DI PERGURUAN TINGGI KABUPATEN GARUT - Lathif, Muhammad Abdul; Kurniawan, Deri Alan; Adiatama, Dani (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This research was conducted to determine the effect of Soft Skills on job readiness, mediated by work motivation, for Fresh Graduates at universities in Garut Regency. The research metho uses a quantitative descriptive approach, where the population includes all Fresh Graduates from universities in Garut Regency, and a sample of 100 people was taken. The sample was selected using a non-probability sampling technique, with the criteria that respondents were male and female Fresh Graduates who graduated in one period in 2024 from universities with "Very Good" accreditation, namely Garut University, the Indonesian Education Institute, and the Garut Institute of Technology. Data was collected through questionnaires, and a Likert scale was used to measure responses. Data analysis was conducted using the PLS-SEM method with SmartPLS 3.0 software. The results of the study show that Soft Skills influence job readiness for Fresh Graduates at universities in Garut Regency, Soft Skills influence work motivation for Fresh Graduates at universities in Garut Regency, work motivation affects job readiness for Fresh Graduates at universities in Garut Regency, and Soft Skills influence job readiness through work motivation as a mediating variable for Fresh Graduates at universities in Garut Regency.